Bank capital structure and credit decisions - Roman Inderst; Holger Müller (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2009)
This paper argues that banks must be sufficiently levered to have first-best incentives to make new risky loans. This result, which is at odds with the notion that leverage invariably leads to excessive risk taking, derives from two key premises that focus squarely on the role of banks as informed lenders. First, banks finance projects that they do not own, which implies that they cannot extract all the profits. Second, banks conduct a credit risk analysis before making new loans. Our model may help understand why banks take on additional unsecured debt, such as unsecured deposits and subordinated loans, over and above their existing deposit base. It may also help understand why banks and finance companies have similar leverage ratios, even though the latter are not deposit takers and hence not subject to the same regulatory capital requirements as banks.
urn:nbn:de:hebis:30-72919
Keywords: G21; G32; 330